A novel method to prepare self‐lubricity of Si3N4/Ag composite: Microstructure, mechanical and tribological properties. Issue 9 (17th April 2018) - Liu, Jiongjie; Wang, Zixi; Yin, Bing; Yang, Jun; Sun, Qichun; Liu, Yulin; Tan, Hui; Qiao, Zhuhui
Abstract: Si3 N4 /Ag composites were firstly prepared through SPS technology, using Si3 N4 and AgNO3 as raw materials. Utilizing the coordination bonding of Ag + ions with nitrogen atoms of Si3 N4, in situ generated Ag particles about 1 μm were tightly anchored on Si3 N4 surface, thereby preventing the outflow of silver during sintering process. Meanwhile, smaller silver particles about 20 nm were located at the grain boundaries of Si3 N4, which effectively improved the mechanical and tribological properties of Si3 N4 ‐based composites. Finally, the Si3 N4 /Ag composites reinforced by Ag particles showed a friction coefficient of 0.48 ± 0.01, wear rate of 1.79 × 10 −6 mm 3 N −1 m −1 and fracture toughness of 7.05 ± 0.2 MPa m 1/2, respectively. Abstract : Schematic diagram about the high dispersion of Ag particles in Si3 N4 matrix.